Linguistic Deviation in Rhyme of Poems in Lewis Carroll‟s Through The Looking-Glass (Language Circle: Journal of Language and Literature, 2018)
One of the identities of a poem is reflected by its author‘s style of writing, including the use of rhymes. How each specific kind of rhymes formed by particular words marks the characteristics of poems, and likewise those in Lewis Carroll‘s Through the Looking-Glass. Therefore, this research aims to delineate the kinds and functions of rhymes and to explicate how Lewis Carroll forms the rhymes from linguistic deviation as his style of writing poems in Through the Looking-Glass. This research applied descriptive qualitative method. The data were taken from poems in Through the Looking-Glass novel. The data were collected by note-taking and phonetic transcription technique. The data were then analyzed to classify the kinds of rhyme and their functions and also to identify the linguistic deviation the author uses to form the rhymes. Lewis Carroll exploits various kinds of rhyme in Through the Looking-Glass, e.g. alliteration, assonance, consonance, euphony, cacophony, eye-rhyme, half-rhyme, perfect rhyme, internal rhyme, end rhyme, masculine rhyme, and feminine rhyme. Those rhymes are utilized to unite the poems, to reinforce and emphasize the author‘s intended meaning, to explain the implied sense and feeling, to clarify the imagery for the readers, to visualize the atmosphere of the poems, and also to achieve the poetic and musical functions. Moreover, in forming those rhymes, he employs phonological deviation, lexical deviation, grammatical deviation, semantic deviation, dialectal deviation, and deviation of historical period as his style of writing poems in Through the Looking-Glass novel.